Himbara Cooperation Activities (Association of State-Owned Banks) in terms of Indonesian Business Competition Law - Septuti Mega Posroito (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Business competition is inevitable when a person or group of people decides to carry out business activities, including banking business. With the formation of Himbara (Association of State-Owned Banks) as an association of banking business actors consisting of Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), State Savings Bank (BTN), and Bank Mandiri can be a threat to banking business actors and customers banking. This can happen when the association has entered into a pricing agreement, payment period agreement, cost compliance, honor/wage agreement; tan profit agreement, business strategy agreement and regional, consumer, or production division agreement which if such a thing is achieved, it will be possible to practice kartel which is anti-competition in nature.  In this study, it will raise the issue of Himbara's p eran in the Indonesian economy as a form of SOE Synergy and analyze the activities of himbara cooperation in terms of the Law of Perrivals Indonesian business.   The cooperation carried out by Himbara needs to be monitored even more closely by the KPPU as an Independent Institution independent of the influence and power of the government and other parties to avoid unfair business competition in the banking world.  The public is also given an open space to make complaints to the KPPU if indeed the activities carried out by Himbara are indicated to be detrimental to customers (service users banking).